Cinemas and Spectators of International Development - Molly Geidel (European Journal of American Studies)
This article tracks how mid-20th century US and Latin American documentary filmmakers created a visual and narrative repertoire that encouraged spectators worldwide to imagine a global transformation from the stagnant living death of underdevelopment to striving, productive life-in-development. It explores how development institutions, theorists, and filmmakers made connections between the experience of spectatorship and the odd mixture of passivity and striving that constituted the ideal “developing” subject. However, it attends not only to the ideal spectators these films attempted to create, but also to the experiences of spectators themselves, concluding that audience reactions to development films, particularly among non-experts, were often skeptical of the universal modernization trajectories on which the films insisted.